2023
DOI: 10.1002/pc.27431
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of additively manufactured polymer composites: A state‐of‐the‐art review and future scope

Vishal Darji,
Shamsher Singh,
Harlal Singh Mali

Abstract: The additive manufacturing (AM) technology can manufacture complex parts with considerable improvements in lead times and lower material wastages. It has enabled technological advances across many domains, from space to medical devices. The polymer composites fabricated through AM have tremendous advantages over conventional polymers in terms of mechanical performance and are, therefore, better suited for producing functional parts and assemblies. However, AM of polymer composites still presents several techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 221 publications
0
7
0
Order By: Relevance
“…Considering that our material is not a highly crosslinked polymer, its reinforcement would be desirable. Some of the additives described in a recent review reported by Darji et al , 48 such as methacrylated wood flour powder, 49 could help to improve the strength and toughness of our photo-polymerized bio-based copolymer. Undoubtedly, additives and plasticizers will affect the material properties and their employment in the DAS : PEGDA composition would be a task for future research.…”
Section: Resultsmentioning
confidence: 93%
“…Considering that our material is not a highly crosslinked polymer, its reinforcement would be desirable. Some of the additives described in a recent review reported by Darji et al , 48 such as methacrylated wood flour powder, 49 could help to improve the strength and toughness of our photo-polymerized bio-based copolymer. Undoubtedly, additives and plasticizers will affect the material properties and their employment in the DAS : PEGDA composition would be a task for future research.…”
Section: Resultsmentioning
confidence: 93%
“…These XRD spectra provide insights into the crystalline characteristics of both the printed and annealed composite specimens. The crystallinity of the printed CFP/PLA composite specimens was examined using the crest in the XRD spectra at a Bragg angle (2 θ ) of 22.5° associated with the lattice plane (2 0 0) 39 . Equations () and () were used to estimate the crystalline size ( L ) and crystallinity index (CI) of the CFP/PLA composite specimens. CI=InormalCIamIC×100% where I am and I c are the intensity of amorphous and crystalline peaks respectively. L=italicKλβcosθ where β is the peak FWHM, θ is the Bragg angle, λ is the radiation wavelength, and K is the dimensionless form factor (0.89).…”
Section: Resultsmentioning
confidence: 99%
“…In the manufacture of the filaments developed in this work, the following materials were used: (a) commercial ABS (acrylonitrile butadiene styrene, Terluran GP35, Ineos™), density at 1.04 g/cm 3 and melt flow rate of 34 g/10 min (220 C/10 kg); (b) beef bone powder (Sander, inc), calcined at 1000 C for removing waste and grease, generating the natural compound hydroxyapatite (HAn) with average particle size of 48 μm (Ca 10 (PO 4 ) 6 (OH) 2 ); (c) alumina (A-1000SG, Almatis) with average size of 0.55 μm, surface area of 7.2 m 2 /g and sintered density of 3.93 g/cm 3 ; (d) zirconia (TZ-3YS, Tosoh, Japan), with average size of 0.59 μm (monomodal), with surface area of 7.2 m 2 /g and sintered density of 6.05 g/cm 3 ; (e) bismuth(-III) carbonate basic (product 10,317, Sigma-Aldrich), with molecular weight of 509,97 g/mol, density of 6.86 g/cm 3 , with average particle size of 14 μm; (f) commercial stearic acid (SA, Synth); (g) carnauba wax (CW, Simoquímica) with density of 0.99 g/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Additive manufacturing (AM) processes, also known as 3D printing, are present in several areas, ranging from small implants to large vehicle parts, passing through branches such as medicine and dentistry. [1][2][3] The solutions presented by these technologies are viable because they are customizable and low-cost. 4 Customization is an essential factor in the health area due to the complexity of human beings, and it is estimated that in the future, hospitals will have bioprinters for transplant demands.…”
Section: Introductionmentioning
confidence: 99%